Recurrent pancreatitis in a patient with familial hypocalciuric hypercalcaemia treated successfully with cinacalcet. - Gunganah, K; Grossman, A; Druce, M (2014)
UNLABELLED: A 22-year-old female student presented with a history of recurrent pancreatitis. The commonest causes of pancreatitis, including drugs, gallstones, corticosteroids, excess alcohol and hypertriglyceridaemia, were excluded. She was found to have an elevated serum calcium level that was considered to be the cause of her pancreatitis, with a detectable serum parathyroid hormone (PTH). An initial diagnosis of primary hyperparathyroidism was made. However, two neck explorations failed to reveal a parathyroid adenoma. She was referred to our unit three years later as her episodes of pancreatitis were becoming more frequent and her calcium level remained persistently elevated. Her investigations were as follows: elevated adjusted calcium level of 2.79 mmol/l (2.2-2.58), PTH level of 4.2 pmol/l (0.6-6.0), low 24 h urine calcium of 0.3 mmol/l and a urine calcium:creatinine ratio of <0.003. A clinical diagnosis of familial hypocalciuric hypercalcaemia (FHH) was made and confirmed on genetic testing that showed a c.1703 G>A mutation in the calcium-sensing receptor gene. Although the hypercalcaemia of FHH is usually without sequelae due to the generalised changes in calcium sensing, in the presence of this complication she was started on cinacalcet 30 mg daily. She had one further episode of pancreatitis with calcium levels ranging between 2.53 and 2.66 mmol/l. Her cinacalcet was gradually increased to 30 mg three times daily, maintaining her calcium levels in the range of 2.15-2.20 mmol/l. She has not had a further episode of pancreatitis for more than 2 years. FHH is usually a benign condition with minimal complications from hypercalcaemia. Pancreatitis has been reported rarely, and no clear management strategy has been defined in these cases. Cinacalcet was successfully used in treating recurrent pancreatitis in a patient with FHH by maintaining calcium levels in the lower part of the reference range. Whether or not this is an effective long-term treatment remains yet to be seen. LEARNING POINTS: FHH is an important differential diagnosis for hypercalcaemia.FHH can rarely cause pancreatitis.No clear strategy is available to help in the management of patients with pancreatitis due to FHH.Cinacalcet was effective in lowering serum calcium levels and reducing the frequency of pancreatitis in our patient with FHH.